Daily and seasonal foraging activity of the oriental non-army ant doryline cerapachys sulcinodis species complex (Hymenoptera: Formicidae) - R. Mizuno (2020)
© 2019 Universidade Estadual de Feira de Santana. All rights reserved. The ant subfamily Dorylinae contains the true army ant genera, the species of which are dominant predators, as well as non-army ants. Some of the non-army ant genera are closely related to true army ants, so they could be an important key in understanding the evolution of the army ant adaptive syndrome. Nevertheless, there has been little field research on the non-army ant doryline species because many of them are very rare. Cerapachys is one of the genera closely related to the Old-World army ants. We found some species of Cerapachys are commonly distributed in northern Thailand, so we investigated the daily and seasonal foraging activities of a non-army doryline ant of Cerapachys sulcinodis species complex in the seasonal tropical area of northern Thailand. Workers of the C. sulcinodis complex were diurnal and actively foraged during the rainy season, and their reproduction and foraging activity paused during the dry season. This report is the first on the foraging activity of non-army doryline ants under field conditions.